Innocent Traffickers, Guilty Victims: The case for prosecuting so-called ‘bottom girls’ in the United States - Levy, Alexandra F (Anti-Trafficking Review, 2016)
Response to ATR Debate Proposition: ‘Prosecuting trafficking deflects attention from much more important responses and is anyway a waste of time and money’